ANALYSIS OF STUDENT SELF-REGULATED LEARNING IN AN EFFORT TO INCREASE THE EFFECTIVENESS OF ONLINE LECTURES IN THE PANDEMIC PERIOD - Yudhie Suchyadi; Nintin Nurlela; Rini Sri Indriani (UNIVERSITAS PAKUAN, 2022)
The purpose of this study was to determine the effectiveness of online learning for students using the Learning Management System (LMS) in terms of problem solving abilities and self-regulated learning in the linear program material for the Education Supervision course. This research was conducted at the Primary School Teacher Education Study Program, Pakuan University in class semester 5A in 2021. This research is an experimental research with 1) One-Shot Case Study methods, to obtain data regarding students' problem solving abilities and 2) One-Group Pretest- Posttest Design, to obtain data regarding student self-regulated learning. Based on the results of the research, 1) online learning with LMS on Educational Supervision material is effective in terms of problem solving abilities of students of the Primary School Teacher Education Study Program, Pakuan University and 2) online learning with LMS on Educational Supervision material from self-regulated learning of students of the Teacher Education Study Program Pakuan University Elementary School.